(untitled) (Al-Qamar, 2021)
This article aims at explicitly explaining the Islamic concept of Hibah. It presents the rulings, opinions, and variant views of the jurists in detail. It has also been compared to its nearest synonyms in English language, i.e., gift and charity. The four conditions that make Hibah valid are discussed with evidence from Islamic jurisprudence, along with the concept of “hold” which is an obligatory aspect of Hiba. The concepts of “resort”, “recur”, their repercussions and the incidents in which these are allowed have also been discussed with proofs from the Ḥadīth. It also encompasses the social issues that may arise when Hibah is not done according to the principles of Islamic Sharīʻah.